Investigation of SCUBE-1 levels in pediatric patients with beta-thalassemia - Acıpayam, Can; Tuncel, Defne Ay; Güneş, Hatice; Seringeç Akkeçeci, Behiye Nurten; İnanç Tolun, Fatma and İpek, Sevcan and Duyuran, Ömer (Journal of Surgery and Medicine, 2019)
Aim: A thrombosis and inflammation marker, Signal peptide-CUB (complement C1r/C1 s)-EGF (epidermal growth factor)-like domain-containing protein 1 (SCUBE-1) is expressed in endothelial cells and activated platelets. We aimed to investigate the levels of this marker in patients with Thalassemia major (TM), a disease which causes a tendency to thrombosis. Methods: Twenty patients with TM and age and gender-matched twenty healthy controls were included in this prospective case-control study. Other thrombosis markers such as D-dimer and homocysteine were studied in addition to SCUBE-1 in both groups. Results: The SCUBE1 and D-dimer levels were higher in the TM group compared to the control group (P=0.004, P=0.023, respectively). A significant positive correlation was detected between platelet count and SCUBE1 (r=0.342, P=0.031). Conclusion: We detected elevated SCUBE1 levels in children with TM compared to the healthy controls, which correlated with platelet count. SCUBE1 may be used as a thrombosis marker in TM in the early stages of the disease.